A Spatio-temporal Analysis of Dowry Crimes in India - Tiwari, Rambooshan; Dixit, Shubham Narayan (Economic and Political Weekly, 2025)
The custom of dowry is deeply rooted in Indian society, and dowry crimes occur all over the country. While the number of dowry deaths has remained almost stable during the 21st century, the incidents of violation of the Dowry Prohibition Act have increase
Keywords: Dowry Crimes; Dowry Prohibition Act; Indian Metropolitan Cities; Dowry Deaths